Challenges and perceptions of depression amongst multi drug resistant TB cases: qualitative study among medical officers of tuberculosis units across the Ahmedabad city, India - Sharma, Rashmi; Bakshi, Harsh; Prajapati, Shailesh; Bhatt, Gneyaa; Mehta, Rajesh; Rami, Kiran; Mehta, Prakash; Shah, Tejas; Dave, Roshni; Pirzada, Azbah (International Journal Of Community Medicine And Public Health, 2021)
Background: Drug resistant tuberculosis (DR-TB), is usually associated with adverse socioeconomic and psychological outcomes. Such patients with co-morbid depression have lower treatment adherence and poor outcomes. Programmatic management of drug resistant tuberculosis (PMDT) guidelines recommend screening of DR-TB patients for mental illnesses at baseline and Follow-up (FU). The objectives were to explore perceptions and experiences of service providers about depression amongst MDR TB cases, review current strategies for screening for depression at Tuberculosis units (TUs) and recommend measures to address depression among MDR TB cases. Methods:This qualitative study was conducted across all TUs of Ahmedabad Municipal Corporation wherein 26 Key informant interviews (KIIs) were conducted using thematic guidelines and subsequently categorized in to subtheme for thematic analysis. Results: MOs had mixed experiences about encountering depression among MDR-TB cases, ranging from 1%-50%. Long duration and side effects of treatment, financial burden due to unemployment and societal stigma were contributory factors. Ensuring compliance was a major challenge. Counselling is an effective intervention for this but lack of counsellors in the program was another challenge. MOs stated that pre-treatment screening for depression is done at DR TB centre, but there is no structured, process. However, most of them don’t do subsequent follow up for depression. Conclusions:More counsellors need to be included in the program and a structured method needs to be devised for screening of depression among MDR TB patients. Both MO TUs and Counsellors need to be sensitized and trained for screening and monitoring depression amongst MDR TB in a systematic way.